2011
DOI: 10.1007/s10008-011-1617-z
|View full text |Cite
|
Sign up to set email alerts
|

Anodic stripping determination of Pt(IV) based on the anodic oxidation of In from electrochemically deposited Pt–In alloy phases

Abstract: A simple, rapid, and sensitive anodic stripping voltammetric method for the determination of Pt (IV) is described. It is based on depositing an intermetallic indium-platinum alloy phase on the surface of a modified graphite electrode, and recording the oxidation peak of indium from that alloy phase with the help of linear scan voltammetry. A systematic study of the behavior of different In-Pt phases revealed that the peak potential of indium oxidation from the different phases can be explained on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In the case of the In-Pt system [1], several intermetallic phases are formed that reduce the range of the concentration of platinum. For the Hg-Pt system, the concentration range of platinum order of magnitude is greater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the In-Pt system [1], several intermetallic phases are formed that reduce the range of the concentration of platinum. For the Hg-Pt system, the concentration range of platinum order of magnitude is greater.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper [1], we have shown that it is possible to determine Pt(IV) by recording the anodic stripping voltammograms of indium oxidation from deposited InPt alloy phases. The determination of platinum is carried out by means of anodic stripping voltammetric methods [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the presence of other metals on the electrode surface forms one or more intermetallic compounds with these metals. Previously we have shown that the determination of platinum, if precipitating it together with indium, is possible 3,4 . In this paper we show the possibility to use copper as a metal activator.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-deposition of platinum was conducted from solutions containing ions of indium (III). Determination of platinum was performed by a pick of selective electro-oxidation of indium from intermetallic compound with platinum [8,9]. To determine gold, a graphite electrode modified by bismuth was used [10].…”
Section: Methodsmentioning
confidence: 99%
“…Determination of platinum ions (IV) by the SV method is carried out by means of electro-deposition of these metals into an alloy with a less precious metal (activator metal) with the following selective electro-oxidation of the activator metal. There have been recorded instances of SV determination of platinum ions (IV) by picks of selective electro-oxidation of mercury [7] or indium [8,9] from intermetallic compounds with platinum.…”
Section: Introductionmentioning
confidence: 99%